Process standardisation for banana wine - Saritha E V (Department of Home Science, College of Horticulture, 2011)
The study on “Process standardisation for banana wine” was undertaken to evaluate the physico chemical and sensory qualities of banana (Palayankodan) wines with pure strains of wine yeast Saccharomyces cerevisiae and commercial baker’s yeast. Since, composition and quality of a wine was closely related to the yeast strain used, standardisation of banana wines with yeast strains was an objective of the study.